TEST TAKING STRATEGY ON STUDENTS’ READING TEST - Muhammad Farhan Rafi; Aang Fatikhul Islam (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2017)
Understanding the meaning of any passage is the aim of reading comprehension. This is one of objectives in Reading 2 class English Department at STKIP PGRI Jombang. To achieve a good score on this subject, students must take a test, they have the answers right in performing reading comprehension test, students could make use of test taking strategy. The research describe what test taking strategy used by students of STKIP PGRI Jombang in performing reading comprehension test are. This study was with Principal Component Analysis (PCA), and descriptive. This research consisted of 95 correspondent of the third-semester students of English Department STKIP PGRI Jombang. It uses questionnaire and test as its instrument. The research found there were 7 factors from 28 strategy items accounted for 69.1% cumulative of the variance. They are Option-Selecting Strategies, Question-Rereading Strategies, Option Comprehension Strategies, Answer-Checking Strategies, Option Consideration Strategies, Cognitive Strategies and Clues-Finding Strategies.